Pengembangan Intrumen Penilaian Higher Order Thinking Skills (HOTS) Berbasis Digital Untuk Meningkatkan Cara Berpikir Kreatif Siswa Kelas XI MIPAS-4 SMA Swasta Masehi Berastagi Tahun Pelajaran 2024/2025. - Sitopu, Juliaman; Hutasuhut, Saidun; Haryadi, Haryadi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Every student's need in higher order thinking must be known by the subject teacher in the classroom. One of the steps used is to develop a digital-based test-based Higher Order Thinking Skill (HOTS) assessment instrument that is prepared based on the needs of each student and subject teacher, where students are required to have a creative way of thinking. The purpose of this study was to develop a digital-based Higher Order Thinking Skilss (HOTS) assessment instrument to improve students' creative thinking, analyze the feasibility of the assessment instrument validation results by material experts, learning design, and evaluation experts, and see the response of students in economic learning activities and keep effectiveness in improving students' creative thinking in class XI MIPAS-4 SMA Swasta Masehi Berastagi. This research model uses Borg and Gall according to the needs of students. The instruments used in this study used validation sheet questionnaires from material, design and evaluation experts, teacher response questionnaires, and student response analysis. On the results of quantitative analysis using validation test, differentiation, and the level of difficulty of the instrument and analysis of experimental data by increasing students' creative thinking. The results obtained from the study showed that the results of multiple choice test validation by material experts were 86% in the very good category, validation by learning design experts were 88% in the very good category, validation results by evaluation experts were 85% in the very good category, teacher response validation results were 89% in the very good category, and student response was 90% in the very good category. This study consisted of students of class XI MIPAS-4 SMA Swasta Masehi Berastagi as many as 30 students. Where the results showed that the digital-based Higher Order Thinking Skills (HOTS) assessment instrument was feasible to use with a total score of 82% in the good category in improving students' creative thinking in economics class XI MIPAS-4 SMA Swasta Masehi Berastagi in the 2024/2025 academic year. Meanwhile, in the control group, the use of LOTS assessment instruments amounted to 56%, which was in the non-creative category in increasing creative thinking in the economic subject of class XI MIPAS-4 SMA Swasta Masehi Berastagi in the 2024/2025 academic year.